A Multi‐Methodological Approach to Determine Permafrost Occurrence and Ground Surface Subsidence in Mountain Terrain, Tyrol, Austria. (22nd June 2016) - Klug, C.; Rieg, L.; Ott, P.; Mössinger, M.; Sailer, R.; Stötter, J.
Abstract: This study evaluates the potential of using high‐resolution remote sensing data to detect permafrost patterns in a recently deglaciated alpine area on the mountain ridge of 'Rofenberg', Tyrol, Austria. Here, small but continuous settling of the surface was detected in differential digital terrain models throughout an annual airborne laser scanning (ALS) data series (2001–11). The settling is hypothesised to result from thawing of perennially frozen ground. To test this hypothesis, we applied a combination of established methods –geomorphological observations, permafrost modelling, near‐surface ground temperature measurements (bottom of the winter snowpack and temperature logging) and geophysical surveys (electrical resistivity tomography, ground penetrating radar, seismic refraction) – that revealed the occurrence of permafrost in recently deglaciated terrain (above 3100 m asl). Consequently, the surface changes detected in the ALS data series are attributed to permafrost thaw and serve as a possible indicator of permafrost occurrence. The applied geophysical measurements also elucidate the recent development of permafrost after glacier recession since the Little Ice Age. However, to prove the existence of permafrost and its possible degradation, ALS data alone are insufficient and a combination of methods is recommended. Copyright © 2016 John Wiley & Sons, Ltd.